Collaborative Experience Between Social Communication and Informatics Engineering in the Educational Videos Production (2020)
The study that gave rise to the research project discussed in this paper is a comparative analysis of visual and textual languages. In this case, the textual calculus PiCO (created in 1996 by Avispa research group at Universidad del Valle and Universidad Javeriana) and the visual calculus GraPiCO (also developed by Avispa in 2000) were used. The project’s goals were to establish in a basic way what perceptions does a user have when confronted with these two types of languages, as well as to find under what circumstances will it be considered that a given language performs better than the other. In this sense, let us remember the popular saying “a picture is worth a thousand words”, but also, “a word tells more tan a thousand images”. To answer these questions, an experiment consisting of several sessions was designed: The top 5 universities in Santiago de Cali were visited and pedagogical workshops, evaluations and surveys were performed. Thus, levels of assimilation, apprehension and acceptance of these two programming languages from a population selected according to certain specific parameters were measured. In order to produce the audiovisual material used in the learning sessions, a methodology was created and adopted for ensuring its communicative efficacy, and it became the main contribution of the study, it is introduced step by step in this paper. It is concluded that the methodology led to the development of effective and convincing audiovisual material.